Measurement Efficiency of Local Government Spending on Poverty Alleviation in Sumatra: Output Oriented Approach With Data Envelopment Analysis - Ratu Eva Febriani; Roosemarina Anggraini Rambe (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
This research aims to measure efficiency of local government spending in poverty alleviation during the COVID-19 pandemic in Sumatra, Indonesia. Data Envelopment Analysis (DEA) was applied as a measurement efficiency method with output-oriented based on variable returns to scale approach.The type of data used in this study is secondary data and implements explanatory analysis. The object of our observation in this study involves total local governments in Sumatra (154 regencies/cities). It used government education spending per capita, health spending per capita, economic spending per capita, and social security spending per capita as input. The Output that we used is the poverty rate. The results show that poverty alleviation through government spending efficiency policy only can achieve by eight local governments, i.e.Deli Serdang, Simalungun, Medan, Sawah Lunto, Pekan Baru, Lampung Tengah, Bangka Barat, and Batam. Pekan Baru is the relatively most efficient regency, while Meranti has the lowest efficiency. 146 inefficient local governments should benchmark to their peer to improve their efficiency score. In addition, differences in the level of efficiency between local governments within one province also need to be inspected.